(untitled) (Homoeopathy for All, 2024)
The prostate is a gland that produces some of the fluid that carries sperm during ejaculation. The prostate gland surrounds the urethra, the tube through which urine passes out of the body. An enlarged prostate means the gland has grown bigger. Prostate enlargement happens to almost all men as they get older. An enlarged prostate is often called benign prostatic hyperplasia (BPH). It is not cancer, and it does not raise your risk for prostate cancer.